Design improvement of thermal management for Li-ion battery energy storage systems. (April 2021) - Ashkboos, Pourya; Yousefi, Amin; Houshfar, Ehsan
Graphical abstract: Highlights: Design optimization of ribbed coolant channel is proposed for Li-ion battery TMS. 3D conjugate heat transfer simulation is employed to explore the effects of ribs. Hydrothermal performance and heat transfer of the battery are improved. The equivalent pumping power is reduced by introducing ribs. Abstract: Thermal management of lithium-ion battery cells provides several advantages to reach high performance electric-vehicles and hybrid-electric-gadgets. Geometrical features and patterns of internal channels of liquid cooling plate (LCP) are key factors for the battery cell cooling efficiency. This paper concerns a new design of battery thermal management and the effect of ribbed channels with double inlets and outlets on the reduction of mass flowrate in the coolant channels of LCP, the hydrothermal performance factor of the battery, the friction coefficient, and the reduction of pumping power by utilizing comprehensive 3D simulations. The Conjugate Heat Transfer approach is employed for the fluid flow and the heat transfer calculations. To enhance the heat transfer surface and cooling efficiency, longitudinal ribs are considered in four different configurations inside the cooling channels. Furthermore, the effects of ribs on the aforementioned parameters in comparison with the non-rib channels are investigated. The results demonstrated that the optimized ribbed configuration increases the total amount of heat transfer by up to 68%, reduces the mass flowrate to 16%, and lowers the pumping power by 20% in comparison with rib-less channels. Meanwhile, the hydrothermal cooling performance factor of enhanced up to 58% and the maximum temperature approximately remains constant.